1991
DOI: 10.1111/j.1476-5381.1991.tb12417.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cromakalim on neurally‐mediated responses of guinea‐pig tracheal smooth muscle

Abstract: 1 The ability of cromakalim to modulate several different types of neuroeffector transmission has been assessed in guinea-pig isolated trachea. 2 In trachea treated with propranolol (10-6M) and indomethacin (2.8 x 10-6M), stimulation of the extrinsic vagal nerves evoked contractions which were blocked by hexamethonium (5 x 10-4M) or by tetrodotoxin (TTX; 10-6M). Cromakalim (10-'M) caused a two fold rightward shift of the frequencyresponse curve.3 In carinal trachea treated with propranolol and indomethacin, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
(32 reference statements)
1
20
1
1
Order By: Relevance
“…In the present study, glibenclamide (0.1-1 I-M) also antagonized the actions of BRL 38227 on responses to EFS in guinea-pig bronchus in a competitive manner. Similarly, previous studies have reported that glibenclamide antagonized the inhibition of NANCe and cholinergic nerve-mediated responses produced by cromakalim in the guinea-pig isolated trachea (Burka et al, 1991;Cooper & Maclagan, 1990) and anaesthetized guinea-pig (Ichinose & Barnes, 1990). These findings lend support to the proposition that the effects of BRL 38227 on responses to EFS are mediated by K+-channel activation, and may further suggest the involvement of an ATP-dependent K+-channel (Quast & Cook, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, glibenclamide (0.1-1 I-M) also antagonized the actions of BRL 38227 on responses to EFS in guinea-pig bronchus in a competitive manner. Similarly, previous studies have reported that glibenclamide antagonized the inhibition of NANCe and cholinergic nerve-mediated responses produced by cromakalim in the guinea-pig isolated trachea (Burka et al, 1991;Cooper & Maclagan, 1990) and anaesthetized guinea-pig (Ichinose & Barnes, 1990). These findings lend support to the proposition that the effects of BRL 38227 on responses to EFS are mediated by K+-channel activation, and may further suggest the involvement of an ATP-dependent K+-channel (Quast & Cook, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of capsaicin to abolish NANCe responses (Andersson & Grundstrom, 1983;Lundberg et al, 1983; Present Study, Figure lb), suggests that the transmitter(s) in this pathway is a sensory neuropeptide (Buck & Burks, 1986), although its identity remains to be established. SP has previously been considered a strong candidate (Lundberg et al, 1983 (Burka et al, 1991) and ketotifen in guineapig bronchus (Kamikawa, 1989 (Kamikawa, 1989;Burka et al, 1991 (Figure 2a). By contrast with its effect on nerve-mediated responses, BRL 38227 was relatively ineffective as a relaxant of ACh-induced tone in the guineapig bronchus (Figure 4), and caused only a small reduction in the response to a challenge with ACh (6 jAM) ( nerve activity in the guinea-pig bronchus, by an action at a prejunctional site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result from the pharmacokinetic properties of BRL55834 and here the observed longlasting effects of BRL55834 compared to those of levcromakalim may be significant. An additional factor is that BRL55834 may depress NANC excitatory neurotransmission in concentrations lower than those required to relax smooth muscle, an effect reported by Burka et al (1991) using levcromakalim. The possibility that such an action of BRL55834 could account for its bronchodilator effects in the absence of the anticipated hypotensive effects (Arch et al, 1994) …”
Section: Discussionmentioning
confidence: 99%
“…One suggestion is that cromakalim inhibits neural mechanisms underlying airways hyper-responsiveness, since available data suggest that cromakalim and other potassium channel activators affect hyper-responsiveness at doses that have no bronchoprotective effect in normal airways (Chapman et al, 1991;Burka et al, 1991). However, irrespective of the effects of the potassium channel activators on airways hyperresponsiveness, they are unequivocally relaxants of normal airways smooth muscle.…”
Section: Discussionmentioning
confidence: 99%